Kingdom of the Netherlands-Aruba : 2010 Article IV Consultation Discussions-Staff Report; Informational Annex; Staff Statement; Public Information Notice on the Executive Board Discussion; and Statement by the Executive Director for the Kingdom of the Netherlands-Aruba. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2010)
Aruba has an open economy with a history of stability-oriented macroeconomic policies. Adverse external shocks have led to a decline in tourism and disruption of oil refinery operations. Serious fiscal challenges need to be addressed and a fiscal adjustment program is needed to safeguard the sustainability of the public finances. Expenditure cuts and the central bank's switch from a credit ceiling to an unremunerated reserves requirement as key policy tool is commended. The new monetary policy framework will likely increase the challenges to prudential regulation and supervision.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet